EFFECTIVENESS OF GIVING DRAGON FRUIT JUICE AND MUNG BEAN PURPOSE ON HEMOGLOBIN LEVELS OF PREGNANT WOMEN IN THE 3RD TEMPO IN THE WORKING AREA OF SADABUAN PUBLIC HEALTH CENTER - Hoirunnisa Tanjung; Litri Artiani; Mutia Sari Lubis; Izmi fadhillah Nasution; Ulfah Hidayah Almadany; Sriyanti Siregar; Tina Marito Harahap (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Anemia in third-trimester pregnant women remains a health problem that increases the risk of maternal and perinatal complications, necessitating alternative interventions based on local food. This study aims to analyze the effectiveness of dragon fruit juice and mung bean porridge on hemoglobin levels in third-trimester pregnant women. The study used a quasi-experimental design with a two-group pretest-posttest. The population consisted of 30 third-trimester pregnant women at the Sadabuan Community Health Center, with a sample of 30 respondents selected using consecutive sampling. Data were collected using observation sheets and a digital hemoglobin meter, then analyzed univariately and bivariately using paired sample t-tests. The results showed that both interventions significantly increased hemoglobin levels (p = 0.000), with a higher increase in the mung bean porridge group than in the dragon fruit juice group. It was concluded that mung bean porridge is more effective as a companion to iron supplementation to increase hemoglobin levels in third-trimester pregnant women